Quantification of SAA1 and SAA2 in lung cancer plasma using the isotype‐specific PRM assays. Issue 18 (17th August 2015) - Kim, Yeoun Jin; Gallien, Sebastien; El‐Khoury, Victoria; Goswami, Panchali; Sertamo, Katriina; Schlesser, Marc; Berchem, Guy; Domon, Bruno
Abstract : The quantification of plasma proteins using the high resolution and accurate mass (HR/AM)‐based parallel reaction monitoring (PRM) method provides an immediate benefit over the conventional SRM‐based method in terms of selectivity. In this study, multiplexed PRM assays were developed to analyze isotypes of serum amyloid A (SAA) proteins in human plasma with a focus on SAA1 and SAA2. Elevated plasma levels of these proteins in patients diagnosed with lung cancer have been reported in previous studies. Since SAA1 and SAA2 are highly homologous, the available immunoassays tend to overestimate their concentrations due to cross‐reactivity. On the other hand, when mass spectrometry (MS)‐based assays are used, the presence of the several allelic variants may result in a problem of underestimation. In the present study, eight peptides that represent the target proteins at three different levels: isotype‐specific (SAA1α, SAA 1β, SAA1γ, SAA2α, SAA2β), protein‐specific (SAA1 or SAA2), and pan SAA (SAA1 and SAA2) were chosen to differentiate SAAs in lung cancer plasma samples using a panel of PRM assays. The measurement of specific isotypes, leveraging the analytical performance of PRM, allowed to quantify the allelic variants of both target proteins. The isotypes detected were corroborated with the genetic information obtained from the same samples. The combination of SAA2α and SAA2β assays representing the total SAA2 concentration demonstrated a superior analytical outcome than the previously used assay on the common peptide when applied to the detection of lung cancer.